Malaysian Students’ Career Interest and Perception towards STEM Programmes and Strategies (International Conference on Computers in Education, 2019)
Malaysia will need one million STEM workers by the year 2020 and eight million workers with STEM skills by 2050. However, Malaysia is suffering from STEM talent depletion due to lack of interest in STEM among students. The Ministry of Education thus implemented various changes to its education system to instil STEM interest among students and introduced STEM programmes and strategies to increase students’ participation in STEM in Malaysia. Therefore, this study aimed to examine students’ career interest and their perception on whether STEM programmes and strategies would enable them to choose a career in STEM. A total of 204 Form Four STEM stream students from Perak, Selangor and Federal State of Kuala Lumpur participated in this study. The data was analysed using MANOVA, followed by ANOVA. The results from MANOVA revealed that there was a statistically significant difference across the states in students’ career interest at p = .02 and their perception on STEM programmes and strategies at p = .01. The findings of this study could be considered for enhancement of STEM initiatives to support STEM education in Malaysia.